Factors Affecting Turnover Intentions Within Gen Z’s Working in Financial Company: Will Job Satisfaction Still Matters? - Satrio Bangun Persada; Fahmi Dwi Prasetyo; Hasna Azizah; Anita Maharani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
High employee turnover, especially among Generation Z, poses a serious challenge for organizational performance in the financial sector. Understanding how compensation, psychological empowerment, and job satisfaction affect turnover intention is essential for effective retention strategies. The purpose of this study was to explore several factors considered to influence turnover intention among Gen Z employees, namely compensation and psychological empowerment, and to examine the potential of job satisfaction as a mediator. This research approach was quantitative, with data collected through an online survey distributed to Generation Z employees specifically working in financial companies. For data analysis, the researcher used the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results of the research indicated that receiving adequate compensation plays a crucial role in reducing employees’ intention to quit their jobs. However, compensation did not significantly increase job satisfaction, indicating that financial rewards alone are not sufficient to drive satisfaction among Generation Z. Conversely, psychological empowerment positively and significantly increased job satisfaction, but did not directly suppress turnover intention. Meanwhile, the link between job satisfaction and turnover intention was not found to be influenced by compensation or empowerment. Instead, factors such as career growth, clarity of purpose, and a healthy work-life balance were deemed to have a stronger impact on Gen Z employees’ decision to stay with a company. The implications of this study suggest the need for effective retention strategies to balance competitive compensation with empowerment initiatives to foster loyalty and satisfaction.